Juridical Analysis Of Enforcement Of State Civil Apparatus (ASN) Discipline In The School Environment (Research Study Of SMA Negeri 15 Batam) - Bungasia Bungasia; Fadlan Fadlan; Darwis Anatami; Erniyanti Erniyanti; Soerya Respationo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Discipline of the State Civil Apparatus has been regulated in Law of the Republic of Indonesia Number 20 of 2023 concerning the State Civil Apparatus. In this regulation, the State Civil Apparatus consists of Civil Servants and Government Employees with Employment Agreements who are appointed by civil service development officials and entrusted with duties in a government position or entrusted with other state duties and are given income based on statutory regulations. The purpose of this regulation is intended to serve as a guideline in enforcing State Civil Service Discipline. However, the reality in the field is that violations of State Civil Apparatus Discipline, especially at SMAN 15 Batam, still occur frequently and repeatedly. This research aims to find out how the law regulates the enforcement of discipline towards State Civil Apparatus in the SMAN 15 Batam environment, how the implementation of law enforcement regarding the application of discipline towards the State Civil Apparatus in the SMAN 15 Batam environment and the obstacles faced by SMAN 15 Batam in enforcing discipline against State Civil Apparatus and alternative problem solving in the form of rewards and punishments. The research method used is a qualitative method with a normative and empirical juridical approach that analyzes statutory regulations relevant to the discipline of the State Civil Service. The data sources for this research were obtained from secondary data and primary data. Primary data was collected through interviews and observations, while secondary data was obtained from previous literature, books, journals and case studies. The results of the research show that so far the process of imposing punishment has only taken the form of a verbal warning delivered directly by the school principal. Verbal warnings are a form of light disciplinary punishment. Verbal warnings are given by considering the background of the Civil Servant disciplinary violation and the impact of the violation. Based on these results, the suggestion put forward is that it is hoped that all State Civil Servants will increase awareness of ASN discipline as well as understand and carry out obligations and avoid prohibitions in accordance with applicable laws and regulations. State civil servants must be more responsible for themselves and in carrying out ASN duties so that the objectives of ASN discipline can be realized well. For example, arriving at school early to avoid unexpected obstacles. In the future, enforcement of discipline in the State Civil Service must really be carried out properly and the process of imposing punishments must be stricter against perpetrators of violations of discipline by the State Civil Service so that it can provide a deterrent effect for undisciplined ASN.